Motivasi Belajar Bahasa Jepang Mahasiswa Program Studi Pendidikan Bahasa Jepang Universitas Muhammadiyah Yogyakarta - Suryadi, Dedi; Rosiah, Rosi (Universitas Muhammadiyah Yogyakarta, 2018)
The learning achievement of Japanese is influenced by internal and external factors. Some of the factors are learning motivation. Low motivation can cause laziness in following the lecture. To be able to know motivation in learning Japanese the research is necessary to obtain an accurate answer. This research is a preliminary study that will focus on How to Motivate Japanese Language Study of Japanese Language Study Program of UMY. The population of this study is the Japanese Language Education Student of UMY which amounts to 104 people spread in 7 classes. The sampling of 60 students is done by proportional random sampling technique. the variables studied in this study is learning motivation. The data source comes from primary and secondary data. The result of this research is Japanese Language Study Program Students Mostly have experience learning Japanese with self study or self-taught. The biggest motivation to learn Japanese is to communicate with Japanese. While the obstacles in the process of learning Japanese is hard to learn Japanese letters such as Hiragana, Katakana and Kanji.Â